(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The objective of this research were to find out the effectiveness of Learning from Error Method to enhance the writing ability and the attitude of the second semester students of English Department of University of Muhammadiyah Bulukumba toward the application of Learning from Error Method in learning writing. The research is restricted to grammatical aspect or language use. The research used Pre-experimental design. It took by using convenience-sampling technique, which chose the class 19 B that consisted of 27 students to be sample. The instrument of the research used the subjective test of writing to know the achievement of the students’ writing ability. The test was having the students write a descriptive paragraph according to the title given. The questionnaire is given to know the attitude of students toward the application of learning from error method to enhance their achievement in writing ability. The result of this research shows that there is significant different between the mean score of the students’ pre-test and the students’ post-test. The result of the t-test indicates that the value 1.39 from the t-test is higher than the t-table 1.315. It means that learning from error method is an effective method in teaching writing. The students have positive attitude toward learning from error method. It is indicated by the result of the questionnaires given to the students, which consist of ten items.